Multidimensional Digital Inclusiveness Index: dimensionality reduction for improved applicability in Digital Agri-solutions - Martins, Carolina Iglésias; Opola, Felix Ouko; Garcia Andarcia, Mariangel; Joshi, Deepa; Muller, A.; Christen, R. (International Water Management Institute, 2024)
This report introduces the refined Multidimensional Digital Inclusiveness Index (MDII), developed to assess and promote inclusiveness in digital innovations within agricultural systems. Developed through iterative consultation with experts and stakeholders, the MDII integrates structural and experiential dimensions of digital inclusiveness. It distinguishes between inclusion — ensuring access and usability — and inclusivity — fostering a sense of belonging and meaningful engagement among diverse underserved groups. By applying theoretical frameworks such as the Capability Approach and the Technology Acceptance Model, the MDII captures the multifaceted nature of digital inclusiveness, addressing both tangible and psychological aspects. The revised framework (Version 3.0) evaluates inclusiveness across seven core dimensions, including accessibility, stakeholder relationships, and the social impacts of digital innovations. Significant refinements have been made to reduce complexity, eliminate redundancies, and introduce actionable core and extended indicators.